GE_GERICHTE C/5893/2015 vom 6. Mai 2016 - GE Cour de justice (2016)
DIVORCE; MESURE PROVISIONNELLE; RELATIONS PERSONNELLES; OBLIGATION D'ENTRETIEN; ENFANT | CC.133.1; CC.176.3; CC.273.1; CPC.276.1; CC.285.1; CPC.227.1; CPC.317.2